Evaluation of communication in web-supported learning communities – an analysis with triangulation research design. (21st December 2006) - Harrer, Andreas; Zeini, Sam; Pinkwart, Niels
In current educational practice, web-based environments are an established means to support learning scenarios. In the study presented in this article, we use them as supporting tools for presence-learning scenarios and investigate the effects of electronic communication forms in this environment. Following the idea of triangulation, we utilised qualitative methods, statistical analysis and Social Network Analysis. Qualitative methods were used to classify the usage types of communication in Wiki and discussion forums. Based on these categories, we selected project groups with maximal variance of their communication behaviour and conducted Social Network Analysis to explore communication structures in detail. This research design is supported by the fact that no single communication form proved to be superior: combined usage produced better results with respect to the final scores. We concluded that more aspects of the respective communication forms should be taken into account to be able to compare them properly.